Development of spin-coated copper iodide on silicon for use in hole-selective contacts. (September 2017) - Gotoh, Kazuhiro; Cui, Min; Takahashi, Isao; Kurokawa, Yasuyoshi; Usami, Noritaka
Abstract: We studied on surface morphology, optical properties and passivation performance of copper iodide (CuI) on crystalline silicon (c-Si) deposited by spin-coating for application to hole-selective contacts to realize high performance and low-cost c-Si solar cells. Absorbance was increased by depositing CuI on c-Si owing to absorption and antireflection effect of CuI. From surface images by scanning electron microscope measurements, discontinuous layer was observed for CuI deposited Si. Effective lifetime was characterized for c-Si with ultra-thin oxide covered by CuI both sides by using a microwave photoconductive decay. The lifetime increased from 2 μs to order of 10 μs by introducing CuI layer possibly due to large conduction band offset.